2018
DOI: 10.1007/s12602-017-9372-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of VSL#3 Probiotic in a Patient with Glycogen Storage Disease Type Ia and Irritable Bowel Disease-like Disease

Abstract: Gut Inflammatory bowel disease (IBD) is a group of chronic gastrointestinal disorders characterised by relapsing and remitting inflammation of the gastrointestinal tract. The two most common types of IBDs are ulcerative colitis and Crohn's disease. Patients with glycogen storage disease (GSD) type Ia present with gastrointestinal symptoms such as recurrent abdominal pain, bloating and changes in stool form or frequency, which is clinically difficult to distinguish from IBD. We report the case of a 36-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It is not known whether these microbiome changes are a cause or a consequence of the pathophysiologies. However, correcting the dysbiosis can improve health in some patients [5052]. Dysbiosis can also provide biomarkers for disease detection and management [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether these microbiome changes are a cause or a consequence of the pathophysiologies. However, correcting the dysbiosis can improve health in some patients [5052]. Dysbiosis can also provide biomarkers for disease detection and management [53].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics supplementation could offer another way to improve and ameliorate the gut microbial population in GSD patients. Carnero-Gregorio and colleagues [14] recently reported a prospective case study pointing toward this direction: by testing a probiotic mixture in a patient with GSD-Ia and Crohn-like IBD, the authors observed a reduced number of bowel episodes and an improvement the patient's quality of life. Moreover, they found a reduction in Enterobacteriaceae relative abundance after the probiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with GSD-Ib may be clinically and metabolically identical to those with GSD-Ia (showing typical physical findings, including protuberant abdomen, truncal obesity, doll-like faces, short stature and hypotrophic muscles [6]), but in addition, most patients with GSD-Ib develop neutropenia and neutrophil dysfunction that predispose them to severe infections and to inflammatory bowel disease (IBD) [11,12]. Although the development of IBD is associated to GSD-Ib, few cases of IBD were recently reported in GSD-Ia [13,14]. Dietary treatment is the cornerstone of GSD-I therapy, and it starts at diagnosis and is life-long.…”
Section: Introductionmentioning
confidence: 99%
“…On a different note, there is a growing interest in the use of probiotics in GSD 1b, but the evidence remains anecdotal (19) . More studies are needed to first more broadly the changes in the composition of the gut microbiota in GSD 1b, and later identify whether there will be any specific indications for probiotics in this group of patients.…”
Section: Discussionmentioning
confidence: 99%